2023
DOI: 10.1002/jsfa.12409
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris polysaccharides modulate gut microbiota and improve metabolic disorders in mice with diet‐induced obesity

Abstract: BACKGROUND Cordyceps militaris is an edible and medicinal fungus, and its polysaccharides are among its main pharmacological components. They can display immunomodulation, anti‐oxidation, anti‐inflammation, anti‐hypolipidemic, and other functions. The anti‐obesity effect of C. militaris polysaccharides (CMP) is not yet fully understood, however. RESULTS In this study, a CMP diet intervention was applied over a 4 week period to mice with obesity induced by a high‐fat diet (HFD), followed by profiling of obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…Hence, the Firmicutes / Bacteroidetes ratio does not seem to be a reliable indicator in the management of obesity. Consistent with previous reports [ 42 , 43 , 44 , 45 ], we found that the abundance of Allobaculum was significantly decreased in HFD-fed mice. However, the abundance of Parabacteroides , Blautia , Streptococcus , and Anaerotruncus , which were positively correlated with obesity, was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the Firmicutes / Bacteroidetes ratio does not seem to be a reliable indicator in the management of obesity. Consistent with previous reports [ 42 , 43 , 44 , 45 ], we found that the abundance of Allobaculum was significantly decreased in HFD-fed mice. However, the abundance of Parabacteroides , Blautia , Streptococcus , and Anaerotruncus , which were positively correlated with obesity, was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…66 VA and RA also decreased the abundance of Allobaculum belonging to the phylum Firmicutes, which is positively related to lipid metabolism, glucose metabolism, and the progression of inflammation. 67,68 Additionally, the administration of the HFD could decrease the abundance of Prevotella, which belongs to the Bacteroidetes phylum. Previous studies have provided evidence that the abundance of Prevotella is relatively higher in MetS patients, and high levels of Prevotella could trigger an inflammatory response and further lead to damage to the gut barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the relative abundance of Lactobacillus and Clostridium_sensu_stricto was decreased after ginsenoside Rb1, CK, and PPD treatment. Meanwhile, previous studies had shown that the relative abundance of Clostridium_XIVa was enhanced in feces of 34 obese subjects with metabolic syndrome than without metabolic syndrome [ 41 ] and Clostridium_XVIII was positively related to obese phenotypes in mice [ 42 ]. Ginsenoside Rb1 and CK treatment reduced the relative abundance of Clostridium_XIVa and Clostridium_XVIII in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 99%